Blood glucose modulation and safety of efferent vagus nerve stimulation in a type 2 diabetic rat model. Issue 8 (19th April 2022) - Payne, Sophie C.; Ward, Glenn; Fallon, James B.; Hyakumura, Tomoko; Prins, Johannes B.; Andrikopoulos, Sofianos; MacIsaac, Richard J.; Villalobos, Joel
Abstract: Vagus nerve stimulation is emerging as a promising treatment for type 2 diabetes. Here, we evaluated the ability of stimulation of the vagus nerve to reduce glycemia in awake, freely moving metabolically compromised rats. A model of type 2 diabetes ( n = 10) was induced using a high‐fat diet and low doses of streptozotocin. Stimulation of the abdominal vagus nerve was achieved by pairing 15 Hz pulses on a distal pair of electrodes with high‐frequency blocking stimulation (26 kHz, 4 mA) on a proximal pair of electrodes to preferentially produce efferent conducting activity (eVNS). Stimulation was well tolerated in awake, freely moving rats. During 1 h of eVNS, glycemia decreased in 90% of subjects (−1.25 ± 1.25 mM h, p = 0.017), and 2 dB above neural threshold was established as the most effective "dose" of eVNS ( p = 0.009). Following 5 weeks of implantation, eVNS was still effective, resulting in significantly decreased glycemia (−1.7 ± 0.6 mM h, p = 0.003) during 1 h of eVNS. There were no overt changes in fascicle area or signs of histopathological damage observed in implanted vagal nerve tissue following chronic implantation and stimulation. Demonstration of the biocompatibility and safety of eVNS in awake, metabolically compromised animals is a critical first step to establishing this therapy for clinical use. With further development, eVNS could be a promising novel therapy for treating type 2 diabetes. Abstract : We demonstrated that our novel vagus nerve stimulation strategy is safe and effective in reducing glycemia, an effect that is repeatable, long‐lasting, and persists despite the continued influence of disease promoting factors, such as a high‐fat diet.